2014
DOI: 10.3233/bme-141190
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating field stimulation promotes spinal cord remyelination by inducing differentiation of oligodendrocyte precursor cells after spinal cord injury

Abstract: Demyelination is part of the cascading secondary injury after the primary insult and contributes to the loss of function after spinal cord injury (SCI). Oligodendrocyte precursor cells (OPCs) are the main remyelinating cells in the central nervous system (CNS). We explored whether oscillating field stimulation (OFS) could efficiently promote OPC differentiation and improve remyelination after SCI. SD rats with SCI induced by the Allen method were randomly divided into two groups, the SCI+OFS group and SCI grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…A recent study showed that the specific stimulation site had different effects on brain network activity. For instance, bilateral rTMS exerted a significant inhibitory effects (23). Our study found myelin sheath loss in several brain areas, including cerebral cortex, corpus callosum, and striatum, was alleviated by magnetic stimulation in cuprizone-treated mice, confirming the protective effects of magnetic stimulation on white matter.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the specific stimulation site had different effects on brain network activity. For instance, bilateral rTMS exerted a significant inhibitory effects (23). Our study found myelin sheath loss in several brain areas, including cerebral cortex, corpus callosum, and striatum, was alleviated by magnetic stimulation in cuprizone-treated mice, confirming the protective effects of magnetic stimulation on white matter.…”
Section: Discussionmentioning
confidence: 99%
“…The most common hardware‐related complications of SCS include electrode migration and infection, followed by lead fracture, cerebrospinal fluid leak, and IPG malfunction; however, the most common motives amongst patients and clinicians for abandoning these systems altogether remain unclear. Comparison of complications associated with SCS placed surgically and SCS placed percutaneously was described by Babu et al; however, patient motives were not a focus of the study . At present, there are limited data distinguishing between the complications associated with the 2 methods; however, most of the available data focus on percutaneous methods.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that oscillating field stimulation (OFS) can promote the recovery of neurological function after SCI in both humans and rodents . Accordingly, our previous studies have shown that OFS can improve the differentiation of OPCs into OLs, leading to the promotion of remyelination and the recovery of neurological function after SCI in rats .…”
mentioning
confidence: 99%